Medium‐sized phosphorus cluster cations P+2m+1 (6 ≤ m ≤ 32) studied by collision‐induced dissociation mass spectrometry. (26th October 2015) - Mu, Lei; Yang, Shumei; Bao, Xiaodi; Yin, Hong; Kong, Xianglei
Abstract : Medium‐sized phosphorus cluster cations were generated by laser ablation of red phosphorus and investigated by the method of collision‐induced dissociation mass spectrometry. Experimental results show that the primary dissociation channels of phosphorus cluster cations ofP + 2 m +1 (6 ≤  m  ≤ 11) are all characterized by the loss of P4 unit. For larger cluster cations, their dissociation pathways were more complex. For those magic cations ofP + 8 k +1 observed previously, their dissociation pathways progressively change from the loss of P4 unit (for k  = 3) to the loss of P8 unit (for k  = 4, 5). A new dissociation pathway characterized by the loss of P10 unit was also indentified for larger cations ofP + 8 k +1 (6 ≤  k  ≤ 8). Theoretical calculation also shows that, for cations ofP + 2 m +1 (4 ≤  m  ≤ 10), the dissociation channel characterized by the loss of P4 unit is more energetically favorable than other dissociation channels, which is in good agreement with the experimental results. Copyright © 2015 John Wiley & Sons, Ltd.